THE IDEA OF FREEDOM IN THE PERIOD OF JADIDISM AT THE END OF XIX AND AT THE BEGINNING OF XX CENTURIES. (Scientific journal of the Fergana State University, 2023)
This article discussed in detail the ideas of independence by the leaders of the movement of Jadism that arose in the second half of the XIX and early XX centuries.